In situ formation of grain boundaries on a supported hybrid to boost water oxidation activity of iridium oxide. Issue 32 (6th August 2021) - Sun, Wei; Wang, Zhiqiang; Tian, Xinlong; Deng, Hui; Liao, Jianjun; Ma, Chenglong; Yang, Ji; Gong, Xueqing; Huang, Weiwei; Ge, Chengjun
Abstract : GB formation between ultrafine NPs plays a critical role in enhancing OER activity. Abstract : Coupling electrochemical water splitting with renewable energy sources shows great potential to produce hydrogen fuel. The sluggish kinetics of the oxygen evolution reaction (OER) resulting from the complicated reaction mechanism and the requirement of the noble metal iridium as the anode catalyst are the two key challenges in implementing proton exchange membrane electrolysis. These challenges may be overcome by the nanoscale design and assembly of novel hybrid materials. Grain boundaries (GBs) are a common crystallographic feature that increase in variability and attractiveness as the particle size decreases. However, the effects of GBs on OER activity in supported hybrid IrO2 catalysts remain unclear. In this study, supported hybrid IrO2 catalysts containing ultrafine nanoparticles were prepared via the self-assembly of iridium precursors on the β-MnO2 surface. The GBs induced intriguing features such as abundant coordination-unsaturated iridium sites and surface hydroxylation, resulting in enhanced OER activity. The formation of GBs was strongly dependent on the nature of the support. In addition to the morphology, the crystal structure of the substrate may play an important role in inducing dense nanoparticle growth. The established relationship between GB formation and OER activity provides an opportunity to design more stable and effective IrO2 -based hybrid materials for the OER.